Development of the Experienced Communication in Dementia Questionnaire: A Qualitative Study - Maria W. L. J. Olthof-Nefkens MSc; Els W. C. Derksen PhD; Bert J. M. de Swart PhD; Maria W. G. Nijhuis-van der Sanden PhD; Johanna G. Kalf PhD (SAGE Publishing, 2021)
Communication problems with their caregivers are common in people with dementia. Although interventions for improvement of communication are being developed, a tool to measure how participants experience their communication is lacking. The objective of this article is to describe the development of a questionnaire that measures the "experienced communication" of persons with dementia (ECD-P) as well as of their caregivers (ECD-C). Interviews were conducted with five person with dementia-caregiver dyads who had recently received a new communication intervention. Reflexive thematic analysis was performed on the transcripts using ATLAS.ti. Codes were created, categories and themes were identified, and items for the questionnaires were generated. Selection of items and response scales was done in collaboration with the same dyads. The final version was established after pilot testing with seven other dyads and discussion with five experts in the field of dementia care. Analysis of the transcripts resulted in 212 codes and 17 categories within four themes: caregiver competence, social communication, communication difficulties in daily life, and experienced emotions during conversations. The final version of the ECD-P consists of part 1 with 22 items and 4-point Likert scales, and part 2 with two items and 1 to 10 scales. In the final ECD-C (proxy version), part 1 and part 2 are similar to the ECD-P, while a part 3 was added to assess caregivers' own perspective and emotions (five items). Based on the experiences of people with dementia and their caregivers, we constructed a face-valid questionnaire. This justifies future research to test its clinimetric characteristics.